Methodology of conducting experimental studies to assess qualitative and quantitative indicators of drawing prism formation - P. A. Grigorev; L. A. Sladkova (Вестник СибАДИ)
Introduction. Based on a full-scale experiment, the process of forming a drawing prism in front of the blade surface was assessed and qualitative indicators that confirm theoretical studies of this process were identified.Materials and methods. In conducting experimental research, the main provisions of the theory of experimental design, based on the methods of mathematical statistics, were used. In accordance with theoretical studies, the process of formation of the drawing prism in front of the working bodies of earth-moving machines is accompanied not only by a change in the speed of soil movement on the surface, which occurs as a result of the action of adhesive forces and frictional forces, but also by the Coriolis acceleration that occurs in the process of moving soil along the curved surface of the dump, which, in our opinion, is the main reason for the uneven distribution of soil in front of the dump surface.Results. The proposed method of conducting and processing the results of the experiment made it possible to identify that the parameters characterizing the force of soil adhesion on the surface of the working body of the dump type are: volumetric mass of soil; the speed of soil movement at the i-th point of the surface of the working body; time of soil movement on the dump surface; coefficient of friction of the soil on the surface of the working body; time of interaction of the soil with the surface of the working body. The method of processing the results of the experiment made it possible to qualitatively identify and quantitatively assess the process of formation of the drag prism when moving soil on the surface of the working body in two-dimensional space, to determine the change in the velocities of soil movement at an arbitrary point of the surface and to verify the working hypothesis and theoretical studies on the nature of the change in the velocities of soil movement in front of the dump surface.Discussions and conclusions. It has been established that in order to reduce stickiness, it is necessary to optimize the parameters of the working body, the depth of digging and the time of interaction of the soil with the surface of the working body.